Cemented paste backfill for mineral tailings management: Review and future perspectives - Qi, Chongchong; Fourie, Andy (Minerals engineering, 2019)
Environmental issues associated with tailings management have made it the most daunting challenge faced by the mining industry. To dispose mineral tailings in a technical, environmental and economical way, the cemented paste backfill (CPB) technology is proposed and widely adopted. Here we summarize recent progress in CPB design, with particular emphasis on flocculation and sedimentation, CPB mix design and CPB pipe transport. We provide an updated picture of underlying mechanisms, experimental techniques, influencing factors and recent frontiers for each abovementioned process. The review concludes with some future directions for the field. We envisage a future in which the CPB design is optimised in an integrated CPB design system, accelerated by artificial intelligence and interpreted using atomic simulation.